Predictors of undiagnosed prevalent type 2 diabetes – The Danish General Suburban Population Study - Heltberg, Andreas (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2018)
• BMI and self-reported cardiovascular disease predicts undiagnosed T2DM. • LRAS is superior than DDRS and FINDRISC in predicting undiagnosed T2DM and SCORE≥5. • SCORE performed best in predicting pre-diabetes. • Low education level was a predictor of undiagnosed T2DM but seems of less importance.